2007
DOI: 10.1093/ndt/gfl839
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin blockade as sole treatment for proteinuric kidney disease in children

Abstract: Background. The traditional management of children with proteinuric kidney disease is treatment with high dose steroids regardless of comorbid conditions such as obesity. This study evaluated the effect of angiotensin blockade (AB) alone as the sole management of children with non-diabetic proteinuric kidney disease. Methods. Retrospective chart analysis was performed in 146 children. Seventeen were identified to have received angiotensin-converting enzyme inhibitor and/ or angiotensin receptor blocker exclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 27 publications
(36 reference statements)
0
18
0
Order By: Relevance
“…It is generally accepted that drugs that interfere with RAS, such as angiotensinconverting enzyme inhibitors and AT 1 -receptor (AT 1 R) blockers, reduce vascular and tubular inflammation in chronic kidney disease (11,13,37), but, in contrast to TTA, these drugs also lower the blood pressure in SHR. An important issue that needs to be explored is whether TTA has any effect on inflammation in hypertension.…”
mentioning
confidence: 99%
“…It is generally accepted that drugs that interfere with RAS, such as angiotensinconverting enzyme inhibitors and AT 1 -receptor (AT 1 R) blockers, reduce vascular and tubular inflammation in chronic kidney disease (11,13,37), but, in contrast to TTA, these drugs also lower the blood pressure in SHR. An important issue that needs to be explored is whether TTA has any effect on inflammation in hypertension.…”
mentioning
confidence: 99%
“…Several interventional trials in adults have shown that dual blockade of the RAAS with ACEI and ARB possesses greater antiproteinuric and renoprotective effects than single blockade with an ACEI even at high doses [7][8]19] . However, in children, only few studies have investigated the efficacy of dual blockade of the RAAS on proteinuria, renal function, BP or cardiac structure with ACEI and ARB [9][10][11][12] . Butani [9] has reported on 3 children with chronic glomerulonephritis treated with a combination of ARB and ACEI without concomitant immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…In children, there are only few studies investigating the efficacy of dual blockade of the RAAS with ACEI and ARB [9][10][11][12] . Therefore, the aim of our study was to investigate whether adding an ARB to proteinuric children already under ACEI treatment may further reduce proteinuria.…”
Section: Introductionmentioning
confidence: 99%
“…[51][52][53] Recent trials confirmed the short-term antiproteinuric efficacy of angiotensin receptor blockers in children from 1 year of age onward. 54, 55 The antiproteinuric response is drug dose-dependent 54 and appears to be quantitatively similar in children with glomerular and nonglomerular disorders.…”
Section: Antiproteinuric Therapymentioning
confidence: 94%